The Effect of Plant Spacing on the Water Status of Soil and Grapevines - Archer, E.; Strauss, H.C. (South African Journal of Enology and Viticulture, 2017)
The effect of plant spacing on soil water content and plant water status is described. The higher root densities of narrower plantings resulted in a more rapid depletion of soil water content. This resulted in a more negative leaf water potential which, in turn, resulted in earlier stomatal closure, affecting transpiration rate negatively. Consequently grapes from narrower spaced vines ripened under higher water stress conditions than those from wider spaced vines.